Mixed-type duality for multiobjective fractional variational control problems - Raman Patel (International Journal of Mathematics and Mathematical Sciences)
The concept of mixed-type duality has been extended to the class of multiobjective fractional variational control problems. A number of duality relations are proved to relate the efficient solutions of the primal and its mixed-type dual problems. The results are obtained for ρ-convex (generalized ρ-convex) functions. The results generalize a number of duality results previously obtained for finite-dimensional nonlinear programming problems under various convexity assumptions.